Hubungan Personal Hygiene Dan Obesitas Terhadap Kejadian Tinea Cruris Pada Pasien di Klinik Amanda Medika Tahun 2023 - Viranti Bibi Zorah; Arif Hidayatullah (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
The incidence of tinea cruris in children varies around the world. It is estimated that about 10-20% of children will experience tinea cruris as in Singapore 13.5%, and and Saudi Arabia 15.1%, in a study in Saudi Arabia tinea cruris is the second most common tinea infection in children. According to PERDOKSI in 2022, Indonesia does not yet have adequate demographic data on the skin condition of Indonesians, in addition to functioning as a form of skin disease surveillance, research on skin conditions is also needed so that handling skin problems can be done more precisely. This study aims to determine the relationship of personal hygiene and obesity to the incidence of tinea cruris in patients at The Amanda Medika Clinic in 2023. This study is a type of quantitative research using case control design. The sampling technique used in this study is Simple Random Sampling with 108 respondents. The results showed that based on The Chi square analysis can be concluded that based on the chi square test above shows the value of Asy Sig (2-tailed) shows the value of 0.048 if < 0.05 means there is a relationship of personal hygiene to the incidence of tinea cruris in patients Amanda Medika Clinic. Based on the chi square test above shows the value of Asy Sig (2-tailed) shows a value of 0.025 if < 0.05 there is a relationship of obesity to the incidence of tinea cruris in patients Amanda Medika Clinic.